Crash into you - McGarry, Katie (Harlequin Teen, 2013)
"[A] good girl with a reckless streak, a street-smart guy with nothing to lose, and a romance forged in the fast lane. The girl with straight As, designer clothes and the perfect life-- that's who people expect Rachel Young to be. So the private-school junior keeps secrets from her wealthy parents and overbearing brothers-- and she's just added two more to the list. One involves racing strangers down dark country roads in her Mustang GT. The other? Seventeen-year-old Isaiah Walker-- a guy she has no business even talking to. But when the foster kid with the tattoos and intense gray eyes comes to her rescue, she can't get him out of her mind. Isaiah has secrets, too. About where he lives, and how he really feels about Rachel. The last thing he needs is to get tangled up with a rich girl who wants to slum it on the south side for kicks-- no matter how angelic she might look. But when their shared love of street racing puts both their lives in jeopardy, they have six weeks to come up with a way out. Six weeks to discover just how far they'll go to save each other" -- from publisher's web site.